Candesartan preserves aortic structure and function in cisplatin-treated rats by upregulating SIRT1/Nrf2/HO-1 signaling and suppressing oxidative stress, TLR-4/NF-κB signaling, and necroptosis - Mahmoud, Ayman M.; Alnasser, Sulaiman M.; Abd El-Ghafar, Omnia A. M.; Alruhaimi, Reem S.; Althagafy, Hanan S.; Atwa, Ahmed M.; Hassanein, Emad H. M. (Frontiers in Pharmacology, 2025)
BackgroundCisplatin (CIS) is widely used in the treatment of several tumors. However, its use is associated with toxicity that contributes to long-term cardiovascular complications in cancer survivors. This study investigated whether the angiotensin II receptor blocker candesartan (CAN) could protect against CIS-induced aortic injury in rats.MethodsRats received CAN (5 mg/kg, oral) for 10 days, with a single intraperitoneal dose of CIS (7 mg/kg) administered on day 7.ResultsHistopathological analysis revealed that CIS induced extensive aortic damage, including endothelial disruption, elastic fiber fragmentation, thrombi, and medial calcification, which were significantly alleviated by CAN. CIS-induced oxidative stress was evidenced by elevated lipid peroxidation, myeloperoxidase (MPO) activity, and suppressed antioxidant defenses, while inflammatory activation was marked by upregulation of TLR-4, NF-κB, iNOS, and pro-inflammatory cytokines. CAN treatment reversed these alterations and restored redox balance and anti-inflammatory cytokine IL-10 levels. CAN enhanced SIRT1/Nrf2/HO-1 signaling and suppressed necroptosis-associated proteins (RIP1, RIP3, MLKL, and caspase-8). Molecular docking supported direct interactions between CAN and SIRT1, Keap1, and HO-1. Additionally, CAN corrected the CIS-induced imbalance in the renin-angiotensin system by decreasing angiotensin (Ang) II and increasing Ang-(1–7), and preserved endothelium-dependent vasorelaxation.ConclusionThese findings suggest that CAN protects against CIS-induced vascular injury through coordinated suppression of oxidative stress, inflammation, and necroptosis, alongside upregulation of SIRT1/Nrf2/HO-1 signaling and restoration of vascular function. CAN may represent a promising vascular-protective strategy in patients undergoing CIS chemotherapy.